Aiding Violence or Peace? The Impact of Foreign Aid on the Risk of Civil Conflict in Sub-Saharan Africa - J. de Ree; E. Nillesen (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2006)
This paper considers the impact of foreign aid on the risk of civil conflict. Previous studies on this topic have not properly addressed the problem of endogeneity between aid and conflict as well as the distorting influences of country specific time invariant effects. We propose GDP levels of donor countries as new and powerful instruments for foreign aid flows in the conflict regression. Aid flows are often defined as a fixed percentage of Donor's GDP hence they are strongly correlated. Changes in donor GDP constitute an exogenous shock to aid received by developing countries, in the sense that it is unrelated to the endogenous aid allocation process. Hence, the identification strategy does not pick up covariation due to aid rationing in the prelude to war. In addition, we condition on a number of macro factors to rule out other possible channels through which donor GDP affects conflict. We find a statistically significant and economically important negative effect of foreign aid on the risk of civil conflict. We estimate that a ten percent increase in foreign aid decreases the risk of civil conflict by six to nine percent using different specifications.
Keywords: 330; Civil conflict; Foreign aid; Sub-Saharan Africa